Levetiracetam: Probably Associated Diurnal Frequent Urination. (March 2016) - Ju, Jun; Zou, Li-Ping; Shi, Xiu-Yu; Hu, Lin-Yan; Pang, Ling-Yu
Abstract : Diurnal frequent urination is a common condition in elementary school children who are especially at risk for associated somatic and behavioral problems. Levetiracetam (LEV) is a broad-spectrum antiepileptic drug that has been used in both partial and generalized seizures and less commonly adverse effects including psychiatric and behavioral problems. Diurnal frequent urination is not a well-known adverse effect of LEV. Here, we reported 2 pediatric cases with epilepsy that developed diurnal frequent urination after LEV administration. Case 1 was a 6-year-old male patient who presented urinary frequency and urgency in the daytime since the third day after LEV was given as adjunctive therapy. Symptoms increased accompanied by the raised dosage of LEV. Laboratory tests and auxiliary examinations did not found evidence of organic disease. Diurnal frequent urination due to LEV was suspected, and then the drug was discontinued. As expected, his frequency of urination returned to normal levels. Another 13-year-old female patient got similar clinical manifestations after oral LEV monotherapy and the symptoms became aggravated while in stress state. Since the most common causes of frequent micturition had been ruled out, the patient was considered to be diagnosed with LEV-associated psychogenic frequent urination. The dosage of LEV was reduced to one-third, and the frequency of urination was reduced by 60%. Both patients got the Naranjo score of 6, which indicated that LEV was a "probable" cause of diurnal frequent urination. Although a definite causal link between LEV and diurnal urinary frequency in the 2 cases remains to be established, we argue that diurnal frequent urination associated with LEV deserves clinician's attention.